Digital Infrastructure, Human Capital, and Entrepreneurial Ecosystem Development in South Korea: A Longitudinal Analysis (2000–2024) - Gianmario Strappati (Westscience Press, 2026)
This study examines the relationship between digital infrastructure, human capital, and entrepreneurial ecosystem development in South Korea between 2000 and 2024. Using longitudinal macroeconomic and technological indicators obtained primarily from the World Bank World Development Indicators database, the research analyzes how digitalization and technological modernization contributed to the transformation of South Korea from a manufacturing-oriented economy into a highly innovation-driven entrepreneurial ecosystem. The empirical analysis combines descriptive longitudinal analysis, correlation analysis, and Ordinary Least Squares (OLS) regression models to evaluate the association between digital infrastructure variables and economic performance. The findings indicate substantial long-term improvements in internet diffusion, broadband infrastructure, secure digital systems, and human capital development. Regression results reveal a positive and statistically significant relationship between internet penetration and GDP growth, supporting existing literature on digital entrepreneurship and innovation ecosystems. Although broadband infrastructure displayed diminishing marginal effects within the regression model, the overall evidence suggests that digital modernization and knowledge-intensive development played important roles in strengthening entrepreneurial competitiveness. The study contributes to entrepreneurship and digital economy literature by providing empirical evidence on the structural determinants of innovation-driven entrepreneurial transformation in South Korea.